The Effects of Responsible Gambling Pop-Up Messages on Gambling Behaviors and Cognitions: A Systematic Review and Meta-Analysis - Bjørseth, Benjamin; Simensen, Josefine Oudmayer; Bjørnethun, Aina; Griffiths, Mark D.; Erevik, Eilin K.; Leino, Tony; Pallesen, Ståle (Frontiers in Psychiatry, 2021)
Pop-up messages utilized by gambling operators are normally presented to gamblers during gambling sessions in order to prevent excessive gambling and/or to help in the appraisal of maladaptive gambling cognitions. However, the effect of such messages on gambling behavior and gambling cognitions has not previously been synthesized quantitatively. Consequently, a meta-analysis estimating the efficacy of pop-up messages on gambling behavior and cognitions was conducted. A systematic literature search with no time constraints was performed on Web of Science, PsychInfo, Medline, PsychNET, and the Cochrane Library. Search terms included “gambling,” “pop-up,” “reminder,” “warning message,” and “dynamic message.” Studies based on randomized controlled trials, quasi-experimental designs and pre-post studies reporting both pre- and post-pop-up data were included. Two authors independently extracted data using pre-defined fields including quality assessment. A total of 18 studies were included and data were synthesized using a random effects model estimating Hedges' g. The effects of pop-ups were g = 0.413 for cognitive measures (95% CI = 0.115–0.707) and g = 0.505 for behavioral measures (95% CI = 0.256–0.746). For both outcomes there was significant between-study heterogeneity which could not be explained by setting (laboratory vs. naturalistic) or sample (gambler vs. non-gamblers). It is concluded that pop-up messages provide moderate effects on gambling behavior and cognitions in the short-term and that such messages play an important role in the gambling operators' portfolio of responsible gambling tools.